2016
DOI: 10.2172/1262491
|View full text |Cite
|
Sign up to set email alerts
|

Digital Architecture Planning Model

Abstract: As part of the U.S. Department of Energy's Light Water Reactor Sustainability Program, the Digital Architecture (DA) Project focuses on providing a model that nuclear utilities can refer to when planning deployment of advanced technologies. The digital architecture planning model (DAPM) is the methodology for mapping power plant operational and support activities into a DA that unifies all data sources needed by the utilities to operate their plants.The DA is defined as a collection of information technology c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The development of the planning model as well as the model itself are described in report INL/EXT-16-38220, Digital Architecture Planning Model. [17] During the 2016 annual NITSL meeting, the scope of the digital architecture project was discussed and it was concluded that it would be very beneficial to the industry for the project to focus more on data analytics. Hence, in FY 2017, the project will develop and evaluate use cases for data mining and analytics for employing information from plant sensors and database for use in developing improved business analytics.…”
mentioning
confidence: 99%
“…The development of the planning model as well as the model itself are described in report INL/EXT-16-38220, Digital Architecture Planning Model. [17] During the 2016 annual NITSL meeting, the scope of the digital architecture project was discussed and it was concluded that it would be very beneficial to the industry for the project to focus more on data analytics. Hence, in FY 2017, the project will develop and evaluate use cases for data mining and analytics for employing information from plant sensors and database for use in developing improved business analytics.…”
mentioning
confidence: 99%